Sustainability of Community Social Resilience in Flood Disaster Mitigation and Adaptation for Global Flood-Prone Communities: Evidence from Kampar Regency, Riau, Indonesia - Arrahmah Dea Syamsaputri; Dedi Hermon (JAMBURA GEO EDUCATION JOURNAL, 2025)
As climate change intensifies and environmental degradation worsens, flooding has transformed from a seasonal event into a persistent and escalating threat. Rural areas are particularly vulnerable due to their limited adaptive capacity and fragile social structures. The increasing frequency and severity of floods underscore the urgent need for both structural reforms and the strengthening of community-based social systems. However, existing studies have not adequately addressed the research gaps, especially concerning how specific components of community social resilience contribute to effective flood disaster management in rural contexts. This study aims to fill that gap by analyzing the role of sustainable community social resilience in managing and adapting to flood disasters in Kampar Regency. The research employs the Rapid Appraisal for Resilience method and analyzes data using Multidimensional Scaling (MDS). It focuses on four key dimensions: social, education, health, and economics. Primary data were collected through interviews with 105 purposively selected respondents from flood-affected communities across 22 subdistricts in Kampar Regency. The results of the multidimensional sustainability index indicate an overall score of 49.06, categorizing the area as “less sustainable.” The dimension-specific scores were as follows: economic (50.29), social (46.08), health (50.10), and education (49.76). These results reveal uneven levels of community resilience, with economic and health dimensions showing slightly better outcomes than others. Tailored interventions addressing dimension-specific weaknesses are essential. Strengthening these localized aspects supports long-term strategies for disaster risk reduction and climate adaptation. This study underscores the importance of incorporating multidimensional assessments into local development planning to build resilience in flood-prone communities.